Sparstolonin B Suppresses Proliferation and Modulates Toll-like Receptor Signaling and Inflammatory Pathways in Human Colorectal Cancer Cells - Bürke Çırçırlı; Çağatay Yılmaz; Tuğçe Çeker; Zerrin Barut; Esma Kırımlıoğlu; Mutay Aslan (Pharmaceuticals)
Background: Sparstolonin B (SsnB), a natural compound with anti-inflammatory and anti-proliferative properties, was investigated for its effects on cell viability, apoptosis, and inflammatory pathways in human colorectal cancer cells (HCT-116) and healthy human fibroblasts (BJ). Phorbol 12-myristate 13-acetate (PMA), a tumor promoter and inflammatory activator, was used to stimulate proliferation and inflammatory pathways. Methods: HCT-116 and BJ cells were treated with SsnB (3.125–50 μM) or PMA (1–10 nM) for 12–18 h. Cell viability was assessed using MTT analysis, while apoptosis was evaluated through cleaved caspase-3 staining, terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL), and flow cytometry. Proliferation was analyzed through proliferating cell nuclear antigen (PCNA) staining. Toll-like receptor (TLR) signaling, cytokine expression, and sphingolipid levels were measured using immunofluorescence, enzyme-linked immunosorbent assay (ELISA), and mass spectrometry, respectively. Results: SsnB reduced HCT-116 cell viability in a dose- and time-dependent manner with minimal effects on BJ cells. SsnB (25 μM, 12 h) decreased HCT-116 viability 0.6-fold, while PMA (10 nM, 12 h) increased it 2-fold (p < 0.01). No significant change was observed in BJ cells. PCNA fluorescence staining increased 2-fold with PMA and decreased 0.4-fold with SsnB (p < 0.001). PMA upregulated TLR2 and TLR4 mRNA and protein levels, with MyD88, p-ERK, and pNF-κB fluorescence increasing 2.1-, 1.5-, and 1.7-fold, respectively (p < 0.001). PMA elevated TNF-α, IL-1β, and IL-6 levels (p < 0.01). SsnB suppressed PMA-induced effects and promoted apoptosis, increasing cleaved caspase-3 levels by 1.5-fold and TUNEL staining by 1.9-fold (p < 0.01). Flow cytometry confirmed a significant increase in early and late apoptotic cells in the SsnB group. SsnB also increased ceramide (C18, C20, C22, and C24) levels (1.3- to 2.5-fold, p < 0.01) while reducing PMA-induced S1P and C1P increases (p < 0.01). Conclusions: SsnB selectively inhibits proliferation, induces apoptosis, and modulates inflammatory and sphingolipid pathways in colorectal cancer cells, with minimal toxicity to healthy fibroblasts, supporting its potential as a targeted therapeutic agent.